French accent through video analysis - Ecklund, Constance L; Wiese, Peter (Foreign Language Annals, 1981)
Abstract  Evaluating a student's accent in a foreign language is a complex process. Although it is obvious to the instructor whether or not the sound is correct, it is difficult for students both to hear the incorrect sound and to correct it. Too often the instructor merely tells the students that they have spoken incorrectly, expresses the sound properly, and then tries, often without lasting success, to have the students imitate. In a phonetically oriented course, diagrams are used as visual aids to teach correct articulation; but, especially at lower levels, it is difficult and often uninspiring for students to identify their speech production with such text figures. In a new method an improvised television “studio” captures the individual student's speech in an easily reviewable, permanent form on videotape. This visual, personal approach can make spectacular improvement in pronunciation, and the technique appears to be adaptable to any level of language learning. © 1981 American Council on the Teaching of Foreign Languages
Keywords: dept.wll